A Case Report of Baclofen Toxicity in a Pediatric Patient With Normal Kidney Function Successfully Treated With Hemodialysis. (August 2020) - Shah, Siddharth A.; Kwon, Stephanie J.; Potter, Katherine E.
Rationale: Baclofen is a commonly prescribed medication used to decrease spasticity in children with cerebral palsy. Despite its widespread use, this medication has not demonstrated to be consistently effective in clinical studies. Baclofen is also associated with systemic adverse effects due to potent neuronal depression. The management of baclofen toxicity is mainly supportive; however, some studies have shown that hemodialysis may alleviate the symptoms of an overdose and shorten the recovery time. Presenting concerns: In this case report, a 6-year-old boy with mild cerebral palsy, neuromyelitis optica, and normal kidney function was found unresponsive at home, with altered mental status, after ingesting 1300 mg of baclofen unobserved. The patient was intubated and mechanically ventilated because of significant neurologic depression with subsequent respiratory failure. Diagnosis: The patient was diagnosed with baclofen-induced encephalopathy. An elevated serum baclofen level of 4.00 µg/mL (therapeutic range of 0.08-0.40 µg/mL) was observed 10 hours after he was found unresponsive. The patient's respiratory status deteriorated; he had high ventilatory requirements and remained comatose. Intervention: With the worsening of his clinical condition in the intensive care unit, hemodialysis, administered via a high-efficiency high-flux dialyzer, was initiated approximately 18 hours after he was found unresponsive. The patient underwent 2 hemodialysis runs spaced 9 hours apart, with blood flow rates approaching 250 mL/min. Outcomes: Within 3 hours of the first hemodialysis treatment, the patient started to regain consciousness. He was extubated to room air 6 hours after the second hemodialysis treatment. Novel findings: Supportive management is the primary treatment of baclofen toxicity in a pediatric patient with normal kidney function. Hemodialysis may be considered in severe cases of baclofen toxicity and worsening clinical status, but further studies are needed to confirm this finding.